Coastal response to Holocene sea-level change: a case study from Singapore - Chua, Stephen (2024)
The deceleration of early to mid-Holocene (10–7 cal. ka BP) relative sea-level rise (RSLR) played a key role in transforming coastal systems from estuaries to deltas. Palaeoenvironmental reconstruction of coastal evolution provide case studies that can help project the response of modern coastal systems to future RSLR. The response of deltas to future RSLR is particularly important to South, Southeast and East Asia which collectively contain 71% of the global coastal population living below 10 m in elevation and 75% of the global coastal floodplain population. However, few Holocene studies of equatorial delta systems exist. Here, we investigate the early to mid-Holocene coastal response to decelerating rates of RSLR through paleoenvironmental reconstruction of the Kallang River Basin, Singapore. We produce a multi-proxy (sedimentology, stable carbon isotope, XRF elemental ratios) record from sediment core MSBH01B to compare with the Holocene relative sea-level record for Singapore. We identify different phases of coastal response through the interplay between accommodation space (A) driven predominantly by RSLR and sedimentation rate (S). In the early Holocene rapid RSLR coupled with low sedimentation rates (A/S = 5.1 ± 0.3) led to mangrove disappearance in the Kallang River Basin coastal area within ∼300 years (9.5–9.2 cal. ka BP). Estuarine sediments were deposited from 9.2 to 8.8 cal. ka BP during continued high rates of RSLR coupled with highest sedimentation rates (A/S = 3.1 ± 0.8) as the coastline retreated. Prodelta sediments were deposited from 8.8 to 8.2 cal. ka BP during decreasing rate of RSLR and high sedimentation rates (A/S = 4.6 ± 5.2). Delta front sediments were deposited during this delta initiation phase from 8.2 to 7.6 cal. ka BP as during a period of low and consistent RSLR and sedimentation rates (A/S = 1.7 ± 0.2). Finally, a prograding delta started forming from 7.6 to 7.2 cal. ka BP during lowest rates of RSLR and sedimentation rates (A/S = 1.7 ± 0.2). Our record provides a case study of possible responses of modern delta systems under a spectrum of predicted sea-level rise scenarios and accompanying sedimentation rates. This study provides an estimated threshold A/S value of 1.7 for coastal retreat to inform policy and mitigation/adaptation measures for Singapore and a simple methodology to obtain local threshold values of other equatorial cities built on floodplain and/or delta systems.